Exposed flame-retardant anti-dripping TPO (thermoplastic polyolefin) waterproof coiled material and preparation method thereof
By using a composite structure of fiber mesh cloth layer and TPO layer in the TPO waterproof coil, and using the synergistic effect of magnesium hydroxide and graphene oxide, the problem of insufficient flame retardant performance of existing TPO waterproof coils is solved, and the further development is achieved High thermal and light stability improve safety.
Patent Information
- Application Number
- CN202411172945.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-23
AI Technical Summary
The flame retardant and exposed properties of existing TPO waterproof coils are insufficient, especially in high temperature environments and produce melt droplets, which poses safety risks, and the dispersion of graphene oxide is poor and difficult to promote industrially.
The composite structure of the fiber mesh cloth layer and the TPO layer is adopted. The flame retardant performance of the fiber mesh cloth layer is improved through the synergistic effect of magnesium hydroxide and graphene oxide, and the PET resin is formed into a mesh structure through crosslinking agent, combining the The flame retardant components and graphene oxide graft polymer in the TPO layer improve dispersion and flame retardant properties.
It significantly improves the flame retardant performance and melting point of TPO waterproof coils, improves the overall thermal stability and light stability, enhances safety, and is suitable for industrial applications.
Smart Images

Figure BDA0005010764560000141 
Figure BDA0005010764560000161
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of waterproofing coiled materials, and in particular, relates to an exposed flame-retardant and anti-melting dripping TPO waterproofing coiled material and a preparation method thereof. Background Art
[0002] Thermoplastic polyolefin (TPO) is a new material that has attracted widespread attention in the waterproofing industry in recent years. It uses a copolymer of ethylene and propylene as the main material. Since the molecular chain of TPO is saturated, the content of tertiary carbon atoms is relatively small, and it does not contain polar atoms, it has chemical stability. In addition, this material has both the good working properties of plastics and the good toughness of rubber, and has a low density and excellent low-temperature toughness. At the same time, it can be processed using conventional equipment. It is a new material with good application prospects.
[0003] However, with the continuous development of the market in recent years and the implementation of the new building waterproofing construction standard "GB 55030-2022", higher requirements have been put forward for many indicators of waterproofing membranes, including the flame retardant performance of waterproofing membranes. For the TPO-P membrane commonly used in single-layer roofs, that is, the membrane with the structure of "TPO layer + reinforcement rib + TPO layer", its flame retardant performance and exposure performance are also put forward higher requirements. Graphene oxide (GO) is a research hotspot. At present, there is a technology that uses graphene oxide (GO) to improve the thermal stability and light stability of TPO waterproofing membranes. However, the existing technology generally uses a multi-step solution method to surface graft and purify graphene oxide, and finally obtains a graphene oxide grafted polymer. This method has the disadvantage that the surface modification of graphene oxide is cumbersome, and for industrial applications, it is not suitable for large-scale promotion and application. In addition, the dispersion of graphene oxide directly added to the TPO layer is poor, the TPO layer and the fiber layer are flammable, and the organic molecules of the TPO layer and the fiber layer are easy to flow and drip under the high temperature generated by combustion, and the safety is poor. Summary of the invention
[0004] The embodiment of the present application provides an exposed flame-retardant and anti-melting dripping TPO waterproof membrane, which can improve the flame-retardant performance and anti-melting dripping performance of the waterproof membrane and the melting point, thereby effectively improving the safety of the TPO waterproof membrane.
[0005] In the first aspect, the present application provides an exposed flame-retardant and anti-drip TPO waterproof coil, comprising: a fiber mesh cloth layer, and a TPO layer arranged on both sides of the fiber mesh cloth layer to cover the fiber mesh cloth layer; wherein, the TPO layer comprises the following components in parts by weight: TPO elastomer, 60 to 80 parts; compatibilizer, 1 to 5 parts; flame retardant component, 3 to 30 parts; antioxidant, 0.1 to 1 part; light stabilizer, 2 to 5 parts; masterbatch, 1 to 4 parts; the fiber mesh cloth layer comprises the following components in parts by weight: PET resin, 60 to 80 parts; magnesium hydroxide, 5 to 20 parts; graphene oxide, 0.1 to 1 part; cross-linking agent, 0.2 to 1 part; PE wax, 0.5 to 2 parts; antioxidant, 0.1 to 0.5 parts.
[0006] According to an embodiment of the first aspect of the present application, the TPO elastomer is selected from Basel CA10A, Basel CA60A, Dow 2300, ExxonMobil 3020, ExxonMobil 3000 or a combination thereof.
[0007] According to an embodiment of the first aspect of the present application, the flame retardant component includes a flame retardant and a TPO functional masterbatch; wherein the flame retardant is selected from magnesium hydroxide, silicone flame retardant, piperazine pyrophosphate, antimony trioxide or a combination thereof.
[0008] According to an embodiment of the first aspect of the present application, magnesium hydroxide may be used alone as a flame retardant.
[0009] According to the embodiment of the first aspect of the present application, the flame retardant uses magnesium hydroxide as the main flame retardant, and one or more of the other flame retardants other than magnesium hydroxide are used as auxiliary flame retardants, wherein the mass ratio of the main flame retardant to the auxiliary flame retardant is (7-10):1.
[0010] According to an embodiment of the first aspect of the present application, the mass ratio of the flame retardant to the TPO functional masterbatch is (1-5):1.
[0011] According to the embodiment of the first aspect of the present application, the particle size of magnesium hydroxide needs to satisfy: 50 ≤1.7μm, D 90 ≤3.5μm.
[0012] According to an embodiment of the first aspect of the present application, the organosilicon flame retardant is selected from SFR 100 halogen-free silicone flame retardant, silicone-based halogen-free transparent liquid flame retardant, transparent silicone flame retardant or a combination thereof.
[0013] According to an embodiment of the first aspect of the present application, the raw materials of the TPO functional masterbatch include thermoplastic polyolefin, maleic anhydride, a cross-linking agent, and graphene oxide in a mass ratio of 1: (0.01-0.03): (0.0025-0.0075): (0.025-0.15).
[0014] According to an embodiment of the first aspect of the present application, the TPO functional masterbatch is prepared according to the following steps:
[0015] Thermoplastic polyolefin, maleic anhydride, crosslinking agent and graphene oxide are dispersed, granulated and extruded at 180° C. to 200° C. in a ratio of 1: (0.01 to 0.03): (0.0025 to 0.0075): (0.025 to 0.15) to obtain a TPO functional masterbatch containing a graphene oxide grafted polymer.
[0016] According to an embodiment of the first aspect of the present application, the cross-linking agent is selected from dicumyl peroxide, dibenzoyl peroxide, di(tert-butylperoxyisopropyl)benzene or a combination thereof.
[0017] According to an embodiment of the first aspect of the present application, the light stabilizer is selected from 2020, UV-234, UV-238, 770 or a combination thereof.
[0018] According to an embodiment of the first aspect of the present application, the PET resin is selected from DuPont 415HP, Shanghai Yuanfang-CH-610, Shanghai Yuanfang-CB-608S, China Resources Chemical CR8816 or a combination thereof.
[0019] According to the embodiment of the first aspect of the present application, the PE wax is selected to have a softening point of 100°C to 115°C.
[0020] According to an embodiment of the first aspect of the present application, the PE wax is selected from Q-18PE, R-110, and Cerelene691.
[0021] According to an embodiment of the first aspect of the present application, the compatibilizer includes one or more of PP-g-MAH, PP-g-GMA, PP-g-PHEMA, POE-g-MAH, and PE-g-MAH.
[0022] According to an embodiment of the first aspect of the present application, the antioxidant is selected from antioxidants 1010, 168, 1076, 246 or a combination thereof.
[0023] According to the embodiment of the first aspect of the present application, the requirements for graphene oxide are: 50 The thickness is 7 to 12 μm, and the number of layers is 1 to 3.
[0024] According to an embodiment of the first aspect of the present application, the monolayer ratio in graphene oxide is greater than 80%.
[0025] According to an embodiment of the first aspect of the present application, the fiber mesh cloth layer needs to meet at least one of the following requirements:
[0026] (1) 100g / m 2 ~150g / m 2 ;
[0027] (2) The minimum unit cell size is 5 mm × 5 mm to 9 mm × 9 mm.
[0028] According to an embodiment of the first aspect of the present application, the width of the fiber mesh cloth layer is 1900 mm to 1980 mm.
[0029] In a second aspect, the present application provides a method for preparing an exposed flame-retardant and anti-melting TPO waterproof membrane, comprising:
[0030] Provide TPO layer;
[0031] Providing a fiber mesh cloth layer;
[0032] The fiber mesh cloth layer covers a surface of one side of the TPO layer and is composited with the TPO layer to obtain a first composite layer;
[0033] In the first composite layer, the side of the fiber mesh cloth layer facing away from the TPO layer covers another TPO layer to prepare an exposed flame-retardant and anti-melting dripping TPO waterproof coiled material.
[0034] According to an embodiment of the second aspect of the present application, providing a TPO layer includes: dispersing the components according to the component ratio of the TPO layer to obtain a raw material mixture; extruding the raw material mixture at 145° C. to 225° C. to obtain the TPO layer. The flame retardant of the flame retardant component and the TPO functional masterbatch are added separately.
[0035] According to an embodiment of the second aspect of the present application, providing a fiber mesh cloth layer includes: dispersing raw materials of the fiber mesh cloth layer according to a formula, and melt blending at 240° C. to 280° C. to prepare a cross-linked highly flame-retardant and anti-melt-drip PET composite material;
[0036] The cross-linked high flame retardant and anti-melting droplet PET composite material is melt-spun at a melt temperature of 270° C. to 330° C. to obtain a cross-linked fiber mesh cloth layer.
[0037] The exposed flame-retardant and anti-melting dripping TPO waterproofing coiled material of the embodiment of the present application, on the one hand, selects magnesium hydroxide as the main flame retardant of the fiber mesh cloth layer without affecting the spinnability of the polyester fiber, and uses a cross-linking agent to cross-link the PET resin to form a mesh structure, effectively improving the flame retardant and anti-melting dripping performance of the PET fiber mesh cloth layer. On the other hand, the TPO layer uses a flame retardant component to be flame-retardant, and cooperates with the fiber mesh cloth layer to prevent the TPO coiled material from dripping after melting, thereby achieving an improvement in the flame retardant performance and melting point of the waterproofing coiled material, that is, having better thermal stability and light stability, thereby effectively improving the overall safety of the exposed flame-retardant and anti-melting dripping TPO waterproofing coiled material. DETAILED DESCRIPTION
[0038] The features and exemplary embodiments of various aspects of the present application will be described in detail below. In order to make the purpose, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only intended to explain the present application, rather than to limit the present application. For those skilled in the art, the present application can be implemented without the need for some of these specific details. The following description of the embodiments is only to provide a better understanding of the present application by illustrating the examples of the present application.
[0039] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the statement "include..." do not exclude the presence of other identical elements in the process, method, article or device including the elements.
[0040] The inventor of the present application found that: there is no flame retardant modification scheme for the reinforcement ribs in TPO waterproofing membranes in the prior art. The inventor of the present application further found that: the key point of graphene oxide playing a flame retardant role in TPO waterproofing membranes is to improve the dispersion of graphene oxide in the TPO waterproofing membrane matrix.
[0041] In order to solve the problems of the prior art, the embodiments of the present application provide an exposed flame-retardant and anti-drip TPO waterproof membrane and a preparation method thereof.
[0042] The following first introduces the exposed flame-retardant and anti-drip TPO waterproof membrane of the embodiment of the present application.
[0043] The exposed flame-retardant and anti-drip TPO waterproof coiled material of the embodiment of the present application includes: a fiber mesh cloth layer, and a TPO layer arranged on both sides of the fiber mesh cloth layer to cover the fiber mesh cloth layer; wherein, the TPO layer includes the following components in parts by weight: TPO elastomer, 60 to 80 parts; compatibilizer, 1 to 5 parts; flame retardant component, 3 to 30 parts; antioxidant, 0.1 to 1 part; light stabilizer, 2 to 5 parts; masterbatch, 1 to 4 parts; in parts by weight, the fiber mesh cloth layer includes the following components: PET resin, 60 to 80 parts; magnesium hydroxide, 5 to 20 parts; graphene oxide, 0.1 to 1 part; cross-linking agent, 0.2 to 1 part; PE wax, 0.5 to 2 parts; antioxidant, 0.1 to 0.5 parts.
[0044] The exposed flame-retardant and anti-melting dripping TPO waterproofing coiled material of the embodiment of the present application, on the one hand, selects magnesium hydroxide as the main flame retardant of the fiber mesh cloth layer without affecting the spinnability of the polyester fiber, and uses a cross-linking agent to cross-link the PET resin to form a mesh structure, effectively improving the flame retardant and anti-melting dripping performance of the PET fiber mesh cloth layer. On the other hand, the TPO layer uses a flame retardant component to be flame-retardant, and cooperates with the fiber mesh cloth layer to prevent the TPO coiled material from dripping after melting, thereby achieving an improvement in the flame retardant performance and melting point of the waterproofing coiled material, that is, having better thermal stability and light stability, thereby effectively improving the safety of the exposed flame-retardant and anti-melting dripping TPO waterproofing coiled material.
[0045] In some embodiments of the present application, the TPO elastomer is selected from Basel CA10A, Basel CA60A, Dow 2300, ExxonMobil 3020, ExxonMobil 3000 or a combination thereof. The exposed flame retardant and anti-melting dripping TPO waterproof membrane prepared by using the above TPO elastomer has good weather resistance and good construction performance.
[0046] In some embodiments of the present application, the flame retardant component includes a flame retardant and a TPO functional masterbatch, wherein the flame retardant is selected from magnesium hydroxide, an organosilicon flame retardant, piperazine pyrophosphate, antimony trioxide or a combination thereof.
[0047] In some embodiments of the present application, the organosilicon flame retardant is selected from SFR 100 halogen-free silicone flame retardant, silicone halogen-free transparent liquid flame retardant, transparent silicone flame retardant or a combination thereof. For example, SFR 100 halogen-free silicone flame retardant purchased from Shanghai Sangjing Chemical Co., Ltd., silicone halogen-free transparent liquid flame retardant purchased from Shenzhen Dianshifang Technology Co., Ltd., and transparent silicone flame retardant purchased from Dongguan Doer New Material Technology Co., Ltd. can be used.
[0048] In some embodiments of the present application, the flame retardant uses magnesium hydroxide as a main flame retardant, and one or more of several other flame retardants other than magnesium hydroxide are used as auxiliary flame retardants, and the mass ratio of the main flame retardant to the auxiliary flame retardant is (7-10):1.
[0049] In the embodiments of the present application, magnesium hydroxide is used as the main flame retardant, which can not only effectively improve the strength of the TPO layer, but also produce a synergistic effect with graphene oxide, thereby effectively improving the flame retardant properties of the TPO layer.
[0050] In some embodiments of the present application, the mass ratio of the flame retardant to the TPO functional masterbatch is (1-5):1.
[0051] In some embodiments of the present application, the raw materials of the TPO functional masterbatch include thermoplastic polyolefin, maleic anhydride, crosslinking agent, and graphene oxide in a mass ratio of 1: (0.01-0.03): (0.0025-0.0075): (0.025-0.15). The TPO functional masterbatch is prepared according to the following steps: thermoplastic polyolefin (TPO), maleic anhydride (MAH), crosslinking agent, and graphene oxide (GO) are dispersed, granulated, and extruded at a mass ratio of 1: (0.01-0.03): (0.0025-0.0075): (0.025-0.15) at 180°C to 200°C to obtain a TPO functional masterbatch containing a graphene oxide grafted polymer (i.e., GO-g-TPO).
[0052] In the exposed flame-retardant and anti-drip TPO waterproof membrane of the embodiment of the present application, the TPO layer is modified by melt blending to obtain a TPO functional masterbatch containing GO-g-TPO functionalization, which effectively improves the dispersibility of graphene oxide in the TPO matrix, thereby enabling the TPO waterproof membrane to achieve a better modification effect, and synergizes with the flame retardant to prevent the TPO membrane from dripping after melting, thereby achieving an improvement in the flame retardant performance and melting point of the waterproof membrane, that is, having better thermal stability and light stability.
[0053] Exemplarily, thermoplastic polyolefin (TPO), maleic anhydride, a crosslinker and graphene oxide (GO) are added to a granulator in a mass ratio of 1: (0.01-0.03): (0.0025-0.0075): (0.025-0.15), the processing temperature of the granulator is 180°C-200°C, the screw speed is 30rpm-50rpm, and then extrusion cooling and granulation are performed to finally obtain a TPO functional masterbatch of GO functionalized with a graphene oxide grafted polymer (i.e., GO-g-TPO).
[0054] In the embodiments of the present application, the TPO functional masterbatch can be physically cross-linked with the TPO molecules in the TPO layer, that is, the graphene oxide grafted polymer (GO-g-TPO) and the TPO resin molecular chains dispersed in the TPO layer are physically cross-linked and entangled, thereby enhancing the cross-linking of the TPO layer itself and playing an anti-dripping and flame retardant role.
[0055] In some embodiments of the present application, the requirements for graphene oxide are: 50The graphene oxide has a thickness of 7 to 12 μm, a number of graphene oxide layers of 1 to 3 layers, and a monolayer rate of graphene oxide greater than 80%. The monolayer rate of graphene oxide refers to the proportion of monolayer graphene oxide in the graphene oxide to the total number of graphene oxide greater than 80%. The use of graphene oxide with a monolayer rate greater than 80% can be fully mixed with the TPO molecules of the TPO layer, and while the flame retardant properties of the TPO layer are enhanced by using a single layer of graphene oxide, the mechanical properties of the TPO layer can also be effectively improved. Among them, the edge position of the graphene oxide with a lamellar structure has abundant hydroxyl and carboxyl groups, which can fully contact with the maleic anhydride-modified TPO to undergo a dehydration reaction, and a TPO functional masterbatch containing a graphene oxide grafted polymer (i.e., GO-g-TPO) is prepared.
[0056] The embodiment of the present application uses a granulator to blend thermoplastic polyolefin, maleic anhydride, a crosslinking agent and graphene oxide for melt grafting polymerization, which can make the dispersion of graphene oxide in TPO functional masterbatch better, greatly improve the dispersion of graphene oxide, and then ensure that graphene oxide is fully in contact with maleic anhydride-modified TPO and undergoes a dehydration reaction, thereby obtaining a TPO functional masterbatch containing GO-g-TPO, which is simpler and more convenient than the multi-step solution method for preparing graphene oxide grafted polymers, and is suitable for industrial production. Subsequently, the TPO functional masterbatch is secondary blended and dispersed with other components in the TOP layer, which can further ensure the dispersion of GO-g-TPO in the TPO functional masterbatch in the TPO layer, and better cooperate with magnesium hydroxide for flame retardancy to obtain a TPO layer. At the same time, the TPO functional masterbatch containing GO-g-TPO is blended with other materials of the TPO layer. While improving the barrier properties of the TPO layer, due to the special structure of GO-g-TPO, it can better physically entangle with the TPO macromolecular chains of the TPO layer, thereby better limiting the activity of the TPO molecular chains and improving the overall thermal stability and anti-dripping properties of the exposed flame retardant and anti-dripping TPO waterproof membrane.
[0057] In some embodiments of the present application, the cross-linking agent is selected from dicumyl peroxide (DCP), dibenzoyl peroxide (BPO), di(tert-butylperoxyisopropyl)benzene (BIBP) or a combination thereof.
[0058] In the embodiment of the present application, the PET resin in the fiber mesh cloth layer is cross-linked by a cross-linking agent to form a mesh structure, thereby improving the anti-melting droplet performance of the fiber mesh cloth layer. At the same time, the technical means of cross-linking with a cross-linking agent directly seals magnesium hydroxide as the main flame retardant in the polyester fiber microstructure of the fiber mesh cloth layer, which can not only effectively improve the strength of the fiber mesh cloth layer, but also effectively improve the flame retardant performance of the fiber mesh cloth layer, completely plugging the flame retardant loopholes in the existing waterproof coiled materials, and effectively improving the flame retardant performance of the waterproof coiled materials.
[0059] In some embodiments of the present application, the particle size of magnesium hydroxide needs to satisfy: 50 ≤1.7μm, D 90 ≤3.5μm. The selection of magnesium hydroxide that meets the above particle size can make magnesium hydroxide as the main flame retardant in the fiber mesh cloth layer play an effective flame retardant role without affecting the spinnability of polyester fiber. Magnesium hydroxide that meets the specified particle size can not only play a synergistic role with TPO functional masterbatch, but also better limit the activity of TPO molecular chains in the TPO layer under high temperature environment, thereby reducing the melt flow rate and achieving the purpose of improving the anti-melting droplet performance of the exposed flame retardant and anti-melting droplet TPO waterproof membrane. At the same time, the graphene oxide with a specific layered structure in the TPO functional masterbatch can be fully dispersed in the TPO layer, which can play a barrier effect, reduce the oxygen permeation rate, and delay the burning speed of the TPO layer. The magnesium hydroxide evenly dispersed in the TPO layer realizes flame retardancy when the TPO layer burns, and cooperates with graphene oxide, thereby effectively improving the flame retardant performance of the exposed flame retardant and anti-melting droplet TPO waterproof membrane.
[0060] In some embodiments of the present application, the light stabilizer is selected from 2020, UV-234, UV-238, 770 or a combination thereof. Adding the light stabilizer can further improve the light stability of the waterproof membrane, prevent the waterproof membrane from being damaged by exposure to external light environment, and increase the service life of the waterproof membrane.
[0061] In some embodiments of the present application, the PET resin is selected from DuPont 415HP, Shanghai Yuanfang-CH-610, Shanghai Yuanfang-CB-608S, China Resources Chemical CR8816 or a combination thereof. The above PET resin can be used to make the fiber mesh cloth layer have appropriate strength, and can also be cross-linked with the TPO molecules of the TPO layer, so that the waterproof roll material as a whole has suitable mechanical properties.
[0062] In some embodiments of the present application, PE wax is selected from PE wax with a softening point of 100°C to 115°C. PE wax is white flake or granular in appearance, and the grades of Q-18PE from Wuhan Xindongyi Chemical Co., Ltd., R-110 from Henan Tianchou Chemical Products Co., Ltd., and Cerelen from Shijiazhuang Guanchi Chemical Technology Co., Ltd. can be selected. e 691 PE wax.
[0063] In some embodiments of the present application, the compatibilizer includes one or more of PP-g-MAH, PP-g-GMA, PP-g-PHEMA, POE-g-MAH, and PE-g-MAH. For example, the compatibilizer can be selected from PP-g-MAH purchased from Sigma-Aldrich, PE-g-MAH purchased from Mitsui Chemicals, and POE-g-MAH purchased from ExxonMobil.
[0064] In some embodiments of the present application, the antioxidant is selected from antioxidants 1010, 168, 1076, 246 or a combination thereof. The antioxidant can further enhance the antioxidant properties of the waterproof membrane, prevent the waterproof membrane from being oxidized when exposed to an outdoor oxidative environment, and effectively increase the service life of the waterproof membrane.
[0065] In some embodiments of the present application, the fiber mesh cloth layer needs to meet at least one of the following requirements:
[0066] (1) 100g / m 2 ~150g / m 2 ;
[0067] (2) The minimum unit cell size is 5 mm × 5 mm to 9 mm × 9 mm.
[0068] In the embodiments of the present application, in order to make the fiber mesh cloth layer have suitable mechanical properties, it is necessary to make it meet the weight requirement of 100g to 150g per square meter. Optionally, to adapt to different flame retardant and waterproof requirements, the size of the minimum unit of the fiber mesh cloth layer is 5mm×5mm to 9mm×9mm. The present application does not limit the thickness of the fiber mesh cloth layer, and the TPO layer and fiber mesh cloth layer of corresponding thickness can be selected according to the requirements of flame retardant and waterproof.
[0069] In some embodiments of the present application, the width of the fiber mesh cloth layer is 1900 mm to 1980 mm.
[0070] In the second aspect, the present application provides a method for preparing an exposed flame retardant and anti-melting dripping TPO waterproof membrane, comprising: providing a TPO layer; providing a fiber mesh cloth layer; composite the surface of one side of the fiber mesh cloth layer covering the TPO layer with the TPO layer to obtain a first composite layer; in the first composite layer, the side of the fiber mesh cloth layer facing away from the TPO layer is covered with a TPO layer to obtain an exposed flame retardant and anti-melting dripping TPO waterproof membrane.
[0071] In some embodiments of the present application, providing the TPO layer includes: dispersing the components according to the component ratio of the TPO layer to obtain a raw material mixture; and extruding the raw material mixture at 145° C. to 225° C. to obtain the TPO layer.
[0072] In the embodiments of the present application, the preparation method of the fiber mesh cloth layer is as follows:
[0073] S1. Add the raw materials of the fiber mesh cloth layer into a mixing device according to the formula for dispersion, and melt blend at 240° C. to 280° C. to prepare a cross-linked highly flame-retardant and anti-melting droplet PET composite material;
[0074] S2. The cross-linked highly flame-retardant and anti-drip PET composite material is melt-spinned, with a melt temperature of 270°C to 330°C, a spinning speed of 1000m / min to 1500m / min, a hot roller traction multiple of 3 to 8 times, an annular cold air temperature of 10°C to 30°C, and a blowing speed of 0.5m / s to 1.5m / s, to finally obtain a cross-linked fiber mesh cloth layer.
[0075] Exemplarily, a method for preparing an exposed flame-retardant and anti-melting dripping TPO waterproofing membrane comprises: according to the component ratio of the TPO layer, adding each component to a high-speed mixer and dispersing them by stirring to obtain a raw material mixture; conveying the mixed raw material mixture to the hopper of the first extruder, and making the first extruder extrude and mold under the conditions of 145°C to 225°C and a screw speed of 10rpm to 40rpm to obtain a TPO layer; compounding the surface of one side of the TPO layer covered with a fiber mesh cloth with the TPO layer to obtain a first composite layer; then, extruding another TPO layer through a second extruder with the same extrusion parameters as the first extruder, and in the first composite layer, the fiber mesh layer covers another TPO layer on the side away from the TPO layer, and calendering and compounding is performed through a pressing roller to form an exposed flame-retardant and anti-melting dripping TPO waterproofing membrane with a three-layer structure of TPO layer-fiber mesh cloth layer-TPO layer. The overall line speed is maintained at 3m / mi n ~6m / m i n After calendering, pulling and winding processes, the exposed flame retardant and anti-drip TPO waterproof membrane can be obtained.
[0076] The exposed flame retardant and anti-melting drip TPO waterproof membrane of the present application adopts the method of adding flame retardant components (magnesium hydroxide and graphene oxide) to the fiber mesh cloth layer and cross-linking the PET resin itself, which effectively improves the problem of flammability and generation of molten droplets in the exposed flame retardant and anti-melting drip TPO waterproof membrane, thereby improving the overall safety of the exposed flame retardant and anti-melting drip TPO waterproof membrane product.
[0077] The following are the raw material components and / or their available sources or abbreviations used in some embodiments: TPO elastomer is Dow 2300. PET resin, model 415HP, purchased from DuPont, USA. Maleic anhydride, abbreviated as MAH. Compatibilizer: PP-g-MAH, purchased from Sigma-Aldrich; PE-g-MAH, purchased from Mitsui Chemicals; POE-g-MAHH, purchased from ExxonMobil. Graphene oxide (GO), model: TL-dcyhsmx, D 50The graphene oxide has a thickness of 7-12 μm; the number of layers of graphene oxide is 1-3, and the monolayer rate is greater than 80%, which is purchased from Shenzhen TuLing JinHua KeJi Technology Co., Ltd. The crosslinking agent is diisopropylbenzene peroxide, the antioxidant is antioxidant 1010, and the light stabilizer is UV-234. The raw materials or components not mentioned in the examples or comparative examples of this application can be obtained through commercial channels and meet the requirements of this application, so they will not be described in detail here.
[0078] Example 1
[0079] Preparation method of fiber mesh cloth layer:
[0080] The component proportions corresponding to the fiber mesh cloth layer of Example 5 in Table 2 were added to the equipment, and melt blended at 260°C to obtain a cross-linked highly flame-retardant and anti-melting PET composite material; the cross-linked highly flame-retardant and anti-melting PET composite material was melt-spun, the melt temperature was 280°C, the spinning speed was 1000m / min, the hot roller drafting multiple was 3 times, the ring-blowing cold air temperature was 15°C, and the blowing speed was 0.5m / s, and finally a cross-linked PET fiber mesh cloth layer was obtained. That is, the fiber mesh cloth layer of Example 1 and Example 5 has the same composition and preparation process.
[0081] Preparation method of TPO functional masterbatch:
[0082] 200 g of TPO, 2 g of maleic anhydride, i.e., MAH, 0.5 g of DCP and 10 g of graphene oxide were added to a small granulator, the processing temperature was 180°C, the screw speed was 30 rpm, and then extrusion cooled and granulated to finally obtain GO-g-TPO, i.e., TPO functional masterbatch containing graphene oxide grafted polymer.
[0083] Preparation method of exposed flame retardant and anti-melting dripping TPO waterproof membrane:
[0084] The upper light-colored formula is added into a high-speed mixer according to the component ratio of the TPO layer, and stirred and dispersed at room temperature to obtain a raw material mixture; the mixed raw material mixture is conveyed to the hopper of the extruder, and the extruder is extruded and molded under the conditions of 150°C to 170°C and a screw speed of 10rpm to obtain a TPO layer; the surface of one side of the fiber mesh cloth layer covering the TPO layer is composited with the TPO layer to obtain a first composite layer; then another TPO layer is extruded through the extruder, and the side of the fiber mesh layer facing away from the TPO layer in the first composite layer is covered with another TPO layer, and calendered and composited by a pressing roller, and the overall linear speed is maintained at 4m / min. After calendering, pulling and winding processes, an exposed flame-retardant and anti-melting dripping TPO waterproof membrane with a three-layer structure of TPO-fiber mesh cloth layer-TPO is formed.
[0085] Example 2
[0086] Provided is an exposed flame retardant and anti-melting dripping TPO waterproof coiled material, wherein the PET fiber mesh cloth layer and the preparation method thereof are the same as those in Example 1, and the preparation method of the exposed flame retardant and anti-melting dripping TPO waterproof coiled material of Example 2 is the same as that in Example 1, the difference between the two is that in the TPO functional masterbatch of the exposed flame retardant and anti-melting dripping TPO waterproof coiled material of Example 2, the amount of DCP used is 0.75 g and the amount of graphene oxide used is 20 g.
[0087] Example 3
[0088] Provided is an exposed flame retardant and anti-melting dripping TPO waterproof coiled material, wherein the PET fiber mesh cloth layer and the preparation method thereof are the same as those in Example 1, and the preparation method of the exposed flame retardant and anti-melting dripping TPO waterproof coiled material in Example 3 is the same as that in Example 1, compared with Example 2, the difference is that in the TPO functional masterbatch of the exposed flame retardant and anti-melting dripping TPO waterproof coiled material in Example 3, the amount of graphene oxide used is 30g.
[0089] Example 4
[0090] Provided is an exposed flame retardant and anti-melting dripping TPO waterproof coiled material, wherein the preparation method of the PET fiber mesh cloth layer is the same as that of Example 1, and the preparation method of the exposed flame retardant and anti-melting dripping TPO waterproof coiled material of Example 4 is the same as that of Example 1, and the difference compared with Example 2 is that in the TPO functional masterbatch of the exposed flame retardant and anti-melting dripping TPO waterproof coiled material of Example 4, the amount of MAH is 4g, the amount of DCP is 1.5g, and the amount of graphene oxide is 30g.
[0091] Comparative Example 1 to Comparative Example 3
[0092] Comparative Examples 1 to 3 all provide an exposed flame-retardant and anti-melting dripping TPO waterproofing membrane, wherein the PET fiber mesh cloth layer and the preparation method thereof are the same as those in Example 1. The preparation methods of the exposed flame-retardant and anti-melting dripping TPO waterproofing membranes in Comparative Examples 1 to 3 are the same as those in Example 1, and compared with Example 2, the difference is that: the TPO functional masterbatch of the exposed flame-retardant and anti-melting dripping TPO waterproofing membrane in Comparative Example 1 does not contain graphene oxide; the flame-retardant component of the exposed flame-retardant and anti-melting dripping TPO waterproofing membrane in Comparative Example 2 does not contain magnesium hydroxide, and the TPO functional masterbatch does not contain graphene oxide; the flame-retardant component of the exposed flame-retardant and anti-melting dripping TPO waterproofing membrane in Comparative Example 3 does not contain magnesium hydroxide, and does not contain TPO functional masterbatch.
[0093] Comparative Example 4
[0094] Provided is an exposed flame-retardant and anti-drip TPO waterproof coiled material, wherein the PET fiber mesh cloth layer and the preparation method thereof are the same as those in Example 1, and the TPO layer is prepared by the same TPO preparation method as in Example 1 according to the ratio of the TPO layer in Comparative Example 4 in Table 1, wherein the flame-retardant component contains only 20 parts of magnesium hydroxide and does not contain TPO functional masterbatch.
[0095] Example 5
[0096] Preparation method of fiber mesh cloth layer:
[0097] The raw materials of the fiber mesh cloth layer are added into the equipment according to the ratio of Example 5 in Table 2, and melt blended at 260°C to obtain a cross-linked highly flame retardant and anti-melting droplet PET composite material; the cross-linked highly flame retardant and anti-melting droplet PET composite material is melt-spun, the melt temperature is 280°C, the spinning speed is 1000m / min, the hot roller drafting multiple is 3 times, the ring blowing cold air temperature is 15°C, and the blowing speed is 0.5m / s, and finally a cross-linked PET fiber mesh cloth layer is obtained.
[0098] Preparation method of TPO functional masterbatch:
[0099] 200 g of TPO, 2 g of MAH, 0.5 g of DCP and 10 g of graphene oxide were added to a small granulator, the processing temperature was 180°C, the screw speed was 30 rpm, and then extrusion cooling and granulation were performed to finally obtain GO-g-TPO, that is, TPO functional masterbatch containing graphene oxide grafted polymer.
[0100] That is, the composition ratio of the TPO layer in Example 1 is used to prepare and serve as the TPO layer in Example 5. Preparation method of the exposed flame retardant and anti-melting dripping TPO waterproof membrane:
[0101] The upper light-colored formula is added into a high-speed mixer according to the component ratio of the TPO layer, and stirred and dispersed at room temperature to obtain a raw material mixture; the mixed raw material mixture is conveyed to the hopper of the extruder, and the extruder is extruded and molded under the conditions of 150℃~170℃ and a screw speed of 10rpm to obtain a TPO layer; the surface of one side of the fiber mesh cloth layer covering the TPO layer is compounded with the TPO layer to obtain a first composite layer; then another TPO layer is extruded and formed by the extruder, and the side of the fiber mesh layer facing away from the TPO layer in the first composite layer is covered with another TPO layer, and the composite is calendered by a pressing roller, and the overall linear speed is maintained at 4m / mi n After calendering, pulling and winding processes, a three-layer structure of TPO-fiber mesh cloth layer-TPO is formed to form an exposed flame retardant and anti-drip TPO waterproof membrane.
[0102] Example 6
[0103] Provided is an exposed flame retardant and anti-melting dripping TPO waterproofing coiled material, wherein the TPO layer and the preparation method thereof are the same as those in Example 5. The preparation method of the exposed flame retardant and anti-melting dripping TPO waterproofing coiled material in Example 6 is the same as that in Example 5, and the difference from Example 5 is that: the components of the fiber mesh cloth layer are different, and the raw materials of the fiber mesh cloth layer are added to the equipment according to the corresponding proportions of the fiber mesh cloth layer in Example 6 in Table 2, and melt blended at 260°C to obtain a cross-linked high flame retardant and anti-melting dripping PET composite material; the cross-linked high flame retardant and anti-melting dripping PET composite material is melt-spun, the melt temperature is 280°C, the spinning speed is 1000m / min, the hot roller drafting multiple is 3 times, the ring blowing cold air temperature is 15°C, and the blowing speed is 0.5m / s, and finally a cross-linked PET fiber mesh cloth layer is obtained.
[0104] Example 7
[0105] Provided is an exposed flame retardant and anti-melting dripping TPO waterproofing coiled material, wherein the TPO layer and the preparation method thereof are the same as those in Example 5. The preparation method of the exposed flame retardant and anti-melting dripping TPO waterproofing coiled material in Example 7 is the same as that in Example 5, and the difference from Example 5 is that: the components of the fiber mesh cloth layer are different, and the raw materials of the fiber mesh cloth layer are added to the equipment according to the proportion of Example 7 in Table 2, and melt blended at 260°C to obtain a cross-linked high flame retardant and anti-melting dripping PET composite material; the cross-linked high flame retardant and anti-melting dripping PET composite material is melt-spun, the melt temperature is 280°C, the spinning speed is 1000m / min, the hot roller drafting multiple is 3 times, the ring blowing cold air temperature is 15°C, and the blowing speed is 0.5m / s, and finally a cross-linked PET fiber mesh cloth layer is obtained.
[0106] Example 8
[0107] Provided is an exposed flame retardant and anti-melting dripping TPO waterproofing coiled material, wherein the TPO layer and the preparation method thereof are the same as those in Example 5. The preparation method of the exposed flame retardant and anti-melting dripping TPO waterproofing coiled material in Example 8 is the same as that in Example 5, and the difference from Example 5 is that: the components of the fiber mesh cloth layer are different, and the raw materials of the fiber mesh cloth layer are added to the equipment according to the proportion of Example 8 in Table 2, and melt blended at 260°C to obtain a cross-linked high flame retardant and anti-melting dripping PET composite material; the cross-linked high flame retardant and anti-melting dripping PET composite material is melt-spun, the melt temperature is 280°C, the spinning speed is 1000m / min, the hot roller drafting multiple is 3 times, the ring blowing cold air temperature is 15°C, and the blowing speed is 0.5m / s, and finally a cross-linked PET fiber mesh cloth layer is obtained.
[0108] Comparative Examples 5 to 7
[0109] Comparative Examples 5 to 7 all provide an exposed flame retardant and anti-melting dripping TPO waterproofing membrane, and the TPO layer and the preparation method thereof are the same as those in Example 5. The preparation methods of the exposed flame retardant and anti-melting dripping TPO waterproofing membranes in Comparative Examples 5 to 7 are the same as those in Example 5, and the PET fiber mesh cloth layers corresponding to Comparative Examples 5 to 7 and the exposed flame retardant and anti-melting dripping TPO waterproofing membranes are prepared according to the proportions of the fiber mesh cloth layers of Comparative Examples 5 to 7 in Table 2 and the preparation method of the fiber mesh cloth layers of Example 5.
[0110] Table 1 Proportions of TPO layers in Examples 1-4 and Comparative Examples 1-4
[0111]
[0112]
[0113] Table 2 Proportions of PET fiber mesh cloth layers of Examples 5-8 and Comparative Examples 5-7
[0114] Components / Quantity Example 5 Example 6 Example 7 Example 8 Comparative Example 5 Comparative Example 6 Comparative Example 7 PET resin 75 75 75 75 75 75 75 Magnesium hydroxide 5 10 10 20 10 0 0 Graphene oxide 0.1 0.25 0.5 1 0 0.5 0 Crosslinking agent 0.5 0.5 0.5 0.5 0.5 0.5 0 PE wax 1 1 1 1 1 1 1 Antioxidants 1 1 1 1 1 1 1
[0115] Performance Testing
[0116] The present application achieves the technical effect of improving the mechanical properties, flame retardant properties and light stability of the overall product of the exposed flame retardant and anti-melting dripping TPO waterproof membrane by combining a TPO layer with a fiber mesh cloth layer. The present application uses the mechanical property retention rate (elongation retention rate) of the exposed flame retardant and anti-melting dripping TPO waterproof membrane samples after UV treatment to measure the light stability differences of the exposed flame retardant and anti-melting dripping TPO waterproof membranes in different embodiments and comparative examples. The flame retardant performance is measured by the temperature corresponding to 5% weight loss of the exposed flame retardant and anti-melting dripping TPO waterproof membrane (T5%), the time required for the burning drippings to ignite the filter paper, and the residual carbon percentage at 600°C (C 600℃ ) for characterization.
[0117] 1. Mechanical properties test
[0118] The mechanical properties test of the exposed flame retardant and anti-drip TPO waterproof membrane samples was carried out in accordance with GB / T 27789-2011. The test items included maximum tensile force, elongation at maximum tensile force, and elongation retention rate.
[0119] UV treatment steps: Place the exposed flame retardant and anti-drip TPO waterproof membrane sample in a xenon arc lamp aging instrument that meets the requirements of GB / T 16422.2, with an irradiation intensity of (60±2)W / m 2(300nm~400nm), black mark temperature is (65±3)℃, light is applied and sprayed for 18min every 2h, the exposed flame retardant and anti-melting TPO waterproof membrane samples are UV treated for a cumulative irradiation time of 14 days, taken out and placed in a (23±2)℃ room for 24h, and then the exposed flame retardant and anti-melting TPO waterproof membrane samples after UV treatment are tested for various items of mechanical properties in accordance with the relevant standards of GB / T 27789-2011. Among them, the maximum tensile force and maximum tensile elongation are tested before UV treatment, and the elongation retention rate is tested after UV treatment.
[0120] 2. Flame retardant performance test
[0121] The initial thermal degradation temperature, i.e. the temperature corresponding to 5% weight loss (T5%), and the residual carbon percentage are characterized by thermal gravimetric testing. The test gas atmosphere is air, the heating rate is 10K / min, and the test temperature range is from room temperature to 600°C.
[0122] The time required for the burning drips to ignite the filter paper is observed and characterized in a flammability test furnace. The test is carried out according to standard GB / T 8626-2007, and the ignition time is 30s.
[0123] 3. Melt Flow Index (MFR) Test
[0124] According to GB / T 3682-2000, the TPO layer and the fiber mesh cloth layer were tested separately. Therefore, the MFR data in Table 3 correspond to the MFR test data of the TPO layer and the fiber mesh cloth layer in the coil, that is, the MFR values of Examples 1-4 and Comparative Examples 1-4 are the MFR values of the TPO layer, and the MFR values of Examples 5-8 and Comparative Examples 5-7 are the MFR values of the micro-mesh cloth layer. The conditions for the melt index (MFR) test are 230°C and a weight of 2.16 kg. Among them, the larger the melt index, the worse the anti-melt droplet performance, and the smaller the melt index, the better the anti-melt droplet performance.
[0125] Table 3 Test results of the exposed flame retardant and anti-drip TPO waterproof membranes of Examples 1 to 8 and Comparative Examples 1 to 7
[0126]
[0127] Note: In Table 3, “--” means that the performance test of the item was not performed.
[0128] The test analysis results are divided into three parts. The first is the effect of changes in a single TPO layer on the overall performance of the exposed flame retardant and drip-resistant TPO waterproof membrane; the second is the effect of changes in the fiber mesh cloth layer on the overall performance of the exposed flame retardant and drip-resistant TPO waterproof membrane; the third is to select the best TPO layer and fiber mesh cloth layer as an example and combine them to compare with the other two samples.
[0129] TPO layer
[0130] Graphene oxide (GO) and magnesium hydroxide (Mg(OH)2) are used as inorganic fillers and have flame retardant effects. Therefore, as shown in the performance test results of Examples 1 to 4 and Comparative Examples 1 to 4 in Table 3, it can be seen that as the amount of graphene oxide (GO) and Mg(OH)2 added in Examples 1 to 4 increases, the maximum tensile force, elongation retention rate and flame retardant performance of the exposed flame retardant and anti-melting droplet TPO waterproof membrane are continuously improved, while the maximum tensile elongation rate is continuously reduced. The flame retardant performance is also improved, among which T 5% , C 600℃ The flame retardant properties and anti-melt dripping properties characterized by the time required for burning drippings to ignite filter paper and melt index have been improved.
[0131] Compared with Comparative Example 4, although the added content of graphene oxide (GO) in Example 2 is less, the TPO functional masterbatch containing graphene oxide (GO) grafted polymer is prepared by melt blending the grafted polymer, which can ensure that GO is better dispersed in the TPO layer, thereby obtaining a better modification effect, so that the exposed flame retardant and anti-melting TPO waterproof membrane has better performance in mechanical properties, light stability and flame retardant properties.
[0132] In terms of the exposed performance of the flame-retardant and anti-melting TPO waterproofing membrane, although the number of added light stabilizers in the TPO layer formula of Example 2 and Example 3 is the same, and the graphene oxide (GO) in Example 3 is slightly more, and graphene oxide (GO) has a good capture effect on the free radicals generated by the photodegradable waterproofing membrane, and has the effect of absorbing and reflecting UV light. Therefore, graphene oxide (GO) can be used as an "auxiliary light stabilizer", thereby effectively improving the overall light stability of the flame-retardant and anti-melting TPO waterproofing membrane when exposed. Therefore, the elongation retention rate of the mechanical properties of the exposed flame-retardant and anti-melting TPO waterproofing membrane in Example 3 is higher than the elongation retention rate of the mechanical properties of the exposed flame-retardant and anti-melting TPO waterproofing membrane in Example 2, proving that it has better light stability than the exposed flame-retardant and anti-melting TPO waterproofing membrane in Example 2.
[0133] In terms of the flame retardant properties and anti-melting dripping properties of the exposed flame retardant and anti-melting dripping TPO waterproof membrane, it can be seen that although the amount of graphene oxide (GO) added in Example 3 is more than that in Example 2, compared with the comprehensive addition amount of magnesium hydroxide, the comprehensive flame retardant properties of the exposed flame retardant and anti-melting dripping TPO waterproof membrane of Example 2 are still better than the comprehensive flame retardant properties of the exposed flame retardant and anti-melting dripping TPO waterproof membrane of Example 3.
[0134] Compared with Comparative Example 1, the flame retardant properties and light aging properties of the exposed flame retardant and anti-melting TPO waterproofing membrane of Example 2 are significantly better, proving that the addition of graphene oxide (GO) can significantly improve the two key properties of the exposed flame retardant and anti-melting TPO waterproofing membrane. The flame retardant component of the exposed flame retardant and anti-melting TPO waterproofing membrane of Comparative Example 2 does not contain magnesium hydroxide and the TPO masterbatch does not contain graphene oxide, and the exposed flame retardant and anti-melting TPO waterproofing membrane of Comparative Example 3 does not contain a flame retardant component, that is, the flame retardant component does not contain magnesium hydroxide and TPO functional masterbatch, and its mechanical properties and flame retardant properties are reduced. Compared with Comparative Examples 2 and 3, the performance test results of Examples 1 to 4 prove that only when magnesium hydroxide and graphene oxide (GO) exist at the same time and the synergistic effect between the two can the flame retardant and anti-melting properties of the exposed flame retardant and anti-melting TPO waterproofing membrane samples be optimally modified.
[0135] By comparing the performance test results of Examples 1 to 4 and Comparative Examples 1 to 4 of the TPO layer, it can be seen that: although the light stability of the exposed flame-retardant and anti-melting TPO waterproofing membrane of Example 3 is superior to that of Example 2, and the flexibility is better. However, the exposed flame-retardant and anti-melting TPO waterproofing membrane of Example 2 meets the requirements of the national standard GB / T 27789-2011 in terms of physical and mechanical properties, and the gap in mechanical properties with the exposed flame-retardant and anti-melting TPO waterproofing membrane of Example 3 is not very obvious, but it has advantages in flame retardant properties and safety properties such as anti-melting. Moreover, the exposed flame-retardant and anti-melting TPO waterproofing membrane of Example 3 adds more graphene oxide (GO), resulting in the increased cost of the exposed flame-retardant and anti-melting TPO waterproofing membrane of Example 3 being higher than the cost of the magnesium hydroxide added in Example 2, and the overall formula cost is higher. Therefore, through comprehensive comparison, it can be seen that the best embodiment of the TPO layer is Example 2.
[0136] Fiber mesh cloth layer
[0137] By comparing the composition of the fiber mesh cloth layer of Examples 5 to 8 in Table 2 and the corresponding performance test results in Table 3, it can be seen that: when the components and contents of the TPO layer remain unchanged, with the increase of the content of magnesium hydroxide and graphene oxide, the fiber mesh cloth layer provides greater strength to the overall sample of the exposed flame retardant and drip-resistant TPO waterproof membrane, the overall tensile strength becomes stronger, and the elongation decreases accordingly.
[0138] Since the light stability is determined by the TPO layer, this section does not discuss the light stability of the exposed flame-retardant and anti-drip TPO waterproof membrane, and its data is consistent with that in Example 1.
[0139] As the content of magnesium hydroxide and graphene oxide increases, the flame retardant performance of the overall sample of the exposed flame retardant and anti-melting TPO waterproof coiled material gradually increases. Compared with Comparative Examples 5 to 7, magnesium hydroxide and graphene oxide exist simultaneously in the fiber mesh cloth layer of the exposed flame retardant and anti-melting TPO waterproof coiled material of Example 7, and there is a cross-linking agent. The two can be fixed in the microstructure of the PET fiber mesh cloth layer under the action of the cross-linking agent, and then give full play to the synergistic flame retardant effect, and the effect of reducing the fluidity of the PET molecular chain, which can effectively improve the flame retardant and anti-melting performance of the fiber mesh cloth layer and the exposed flame retardant and anti-melting TPO waterproof coiled material as a whole, so it can effectively improve the flame retardant performance of the exposed flame retardant and anti-melting TPO waterproof coiled material. It can also be seen from the MFR test data that the anti-melting effect of the fiber mesh cloth layer of Example 7 is better than the anti-melting effect of the fiber mesh cloth layer of Comparative Examples 5 to 7, proving that the method of adding magnesium hydroxide and graphene oxide to the formula of the PET fiber mesh cloth layer, and under the action of the cross-linking agent, can give full play to the effect of improving flame retardant performance and anti-melting performance. By comparing the data, it can be seen that although the flame retardant and anti-melting droplet TPO waterproof membrane of Example 8 is better in flame retardancy and anti-melting droplet, its physical and mechanical properties are significantly attenuated compared with the exposed flame retardant and anti-melting droplet TPO waterproof membrane of Example 7. Therefore, this section selects the fiber mesh cloth layer of Example 7 as the best choice.
[0140] In order to further verify the influence of the composite TPO layer and the fiber mesh cloth layer on the overall performance of the exposed flame retardant and anti-melting TPO waterproofing membrane. The TPO layer of Example 2 and the fiber mesh cloth layer of Example 7 were used to prepare the corresponding exposed flame retardant and anti-melting TPO waterproofing membrane samples. From the performance test results in Table 3, it can be seen that the mechanical properties of the overall sample of the exposed flame retardant and anti-melting TPO waterproofing membrane are better, but the elongation is reduced; in terms of flame retardant performance and anti-melting performance, it is significantly improved compared with the exposed flame retardant and anti-melting TPO waterproofing membrane of Example 2, proving that the corresponding exposed flame retardant and anti-melting TPO waterproofing membrane samples prepared by using the optimal formula of fiber mesh cloth and the optimal TPO layer formula can effectively improve the flame retardant and anti-melting performance of the samples, and the overall thermal stability of the exposed flame retardant and anti-melting TPO waterproofing membrane is also improved, which is also helpful for the service life of the exposed flame retardant and anti-melting TPO waterproofing membrane under long-term high temperature and light conditions outdoors.
[0141] The above is only a specific implementation method of the present application. Those skilled in the art can clearly understand that for the convenience and simplicity of description, the specific working process described above can refer to the corresponding process in the aforementioned method embodiment, and will not be repeated here. It should be understood that the protection scope of the present application is not limited to this. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application.
Claims
1. An exposed flame retardant and anti-drip TPO waterproof membrane, characterized in that: include: A fiber mesh cloth layer, and a TPO layer disposed on both sides of the fiber mesh cloth layer to cover the fiber mesh cloth layer; wherein, In parts by weight, the TPO layer comprises the following components: TPO elastomer, 60-80 parts; Compatibilizer, 1 to 5 parts; Flame retardant component, 3 to 30 parts; Antioxidant, 0.1-1 part; Light stabilizer, 2-5 parts; Masterbatch, 1 to 4 parts; The fiber mesh cloth layer comprises the following components in parts by weight: PET resin, 60-80 parts; Magnesium hydroxide, 5-20 parts; Graphene oxide, 0.1-1 part; Cross-linking agent, 0.2-1 part; PE wax, 0.5-2 parts; Antioxidant, 0.1-0.5 parts.
2. The exposed flame-retardant and anti-drip TPO waterproof membrane according to claim 1, characterized in that: The TPO elastomer is selected from Basel CA10A, Basel CA60A, Dow 2300, ExxonMobil 3020, ExxonMobil 3000 or a combination thereof.
3. The exposed flame-retardant and anti-drip TPO waterproof membrane according to claim 1, characterized in that: The flame retardant component comprises a flame retardant and a TPO masterbatch; wherein the flame retardant is selected from magnesium hydroxide, an organic silicon flame retardant, piperazine pyrophosphate, antimony trioxide or a combination thereof.
4. The exposed flame-retardant and anti-drip TPO waterproof membrane according to claim 3, characterized in that: At least one of the following requirements must be met: The particle size of the magnesium hydroxide must satisfy: 50 ≤1.7μm, D 90 ≤3.5μm; The flame retardant uses magnesium hydroxide as a main flame retardant and one or more of several other flame retardants other than magnesium hydroxide as auxiliary flame retardants, and the mass ratio of the main flame retardant to the auxiliary flame retardant is (7-10):1; The mass ratio of the flame retardant to the TPO functional masterbatch is (1-5):1; The raw materials of the TPO functional masterbatch include thermoplastic polyolefin, maleic anhydride, crosslinking agent, and graphene oxide in a mass ratio of 1: (0.01-0.03): (0.0025-0.0075): (0.025-0.15); The organic silicon flame retardant is selected from SFR 100 halogen-free silicon flame retardant, silicon-based halogen-free transparent liquid flame retardant, transparent silicone flame retardant or a combination thereof.
5. The exposed flame-retardant and anti-drip TPO waterproof membrane according to any one of claims 1 to 4, characterized in that: Meet any of the following requirements: The light stabilizer is selected from 2020, UV-234, UV-238, 770 or a combination thereof; The compatibilizer is selected from PP-g-MAH, PP-g-GMA, PP-g-PHEMA, POE-g-MAH, PE-g-MAH or a combination thereof.
6. The exposed flame-retardant and anti-drip TPO waterproof membrane according to any one of claims 1 to 4, characterized in that: The crosslinking agent is selected from dicumyl peroxide, dibenzoyl peroxide, di(tert-butylperoxyisopropyl)benzene or a combination thereof.
7. The exposed flame-retardant and anti-drip TPO waterproof membrane according to any one of claims 1 to 4, characterized in that: Meet any of the following requirements: The requirements for graphene oxide are: 50 7μm~12μm, 1~3 layers; The monolayer ratio of the graphene oxide is greater than 80%.
8. The exposed flame-retardant and anti-drip TPO waterproof membrane according to any one of claims 1 to 4, characterized in that: Meet any of the following requirements: The PET resin is selected from DuPont 415HP, Shanghai Yuanfang-CH-610, Shanghai Yuanfang-CB-608S, China Resources Chemical CR8816 or a combination thereof; The antioxidant is selected from antioxidants 1010, 168, 1076, 246 or a combination thereof; The PE wax is selected from PE wax having a softening point of 100°C to 115°C.
9. The exposed flame-retardant and anti-drip TPO waterproof membrane according to any one of claims 1 to 4, characterized in that: The fiber mesh cloth layer meets at least one of the following requirements: (1)100g / m 2 ~150g / m 2 ; (2) The minimum unit cell size is 5 mm × 5 mm to 9 mm × 9 mm.
10. A method for preparing the exposed flame-retardant and anti-drip TPO waterproofing membrane according to any one of claims 1 to 9, characterized in that: include: Provide TPO layer; Providing a fiber mesh cloth layer; Compounding one side of the fiber mesh cloth layer covering a TPO layer with the TPO layer to obtain a first composite layer; In the first composite layer, the side of the fiber mesh cloth layer facing away from the TPO layer covers another TPO layer, so as to obtain an exposed flame-retardant and anti-melting dripping TPO waterproof coiled material.
Citation Information
Patent Citations
Fire-retardant thermoplastic polyolefin waterproof roll and preparation method thereof
CN104441887A
Flame-retardant modified TPO (Thermoplastic Polyolefin) waterproof roll and preparation method thereof
CN106221021A
Method for preparing flame-retardant melt-proof coated textile fabric
CN106811956A
Raphene-modified polyester blended fabrics and preparation method thereof
CN107190382A
Fireproof wear-resistant fabric
CN110499650A
